Solid Waste Management of Public Secondary Schools in Pili East District, Philippines - Serillano, Raquel Lozano (MANDALIKA : Journal of Social Science, 2025)
The study used the descriptive, evaluative, and correlational research design to determine the level of respondents' awareness, practices, and extent of implementation of Solid Waste Management (SWM) of Public Secondary Schools in Pili East District for SY 2023-2024. The quantitative data were gathered from 180 teachers, 180 students, 180 Parents, seven non-teaching Staff, and seven Barangay Officials. A survey questionnaire was used to gather the needed data. The statistical tools used in the analysis of the data were the 4-point Likert scale, weighted mean, spearman correlation, percentage, and rank. The results revealed that the level of respondents' awareness of SWM Practices as perceived by the school population was high, and the extent of implementation of SWM practices was very good. In addition to this, a significant relationship was noted between the level of awareness and the extent of implementation of SWM. Along with the implementation of SWM, some facilitating and limiting factors were encountered. Proposed recommendations were made to enhance the implementation of SWM. It can be concluded that the level of awareness greatly influenced the extent of implementation of SWM practices by Public Secondary Schools in Pili East District. Thus, relevant recommendations were made based on the results of the study.